2009
DOI: 10.1530/eje-08-0620
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-associated hyperparathyroidism: report of four cases and review of the literature

Abstract: Context: Lithium-associated hyperparathyroidism (LAH) was first described in 1973 but many issues remain in question regarding the pathophysiology as well as the appropriate management of this condition. Objective: Report of four new cases and review of the literature. Results: We describe two males and two females, treated for more than 10 years with lithium due to bipolar disorder, who developed LAH. All underwent parathyroidectomy. In three cases (75%), pathology revealed multiglandular disease, with hyperp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 33 publications
3
98
0
4
Order By: Relevance
“…This condition is in agreement with the explanation proposed by some studies, which say that the HPT induced by Li has no relation to the given therapeutic dose, but rather with the presence of the medication in the body (34,35). The duration of the treatment increases the incidence of this clinical condition due to the cumulative power that Li has on the body (19,36).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This condition is in agreement with the explanation proposed by some studies, which say that the HPT induced by Li has no relation to the given therapeutic dose, but rather with the presence of the medication in the body (34,35). The duration of the treatment increases the incidence of this clinical condition due to the cumulative power that Li has on the body (19,36).…”
Section: Discussionsupporting
confidence: 92%
“…In Li users who have been using it for at least 10 years, the prevalence of HPT was observed in approximately 10-15%, being higher in women (4:1), with the occurrence of both hyperplasia and adenomas of the parathyroid glands (18,19). In confirming diagnoses of lithium-associated hyperparathyroidism, therapeutic decisions should be individualized, taking as an initial choice suspension of Li in symptomatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…McHenry et al have reported that 80% of patients treated with lithium for 6 to 24 months experience a 10% increase in serum calcium levels. Christiansen et al re-ported that both serum calcium and PTH levels increased by 30% in the same population, and several other authors have also reported a 10% -60% increased prevalence of hypercalcemia and hyperparathyroidism in patients taking lithium [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Even with normal or low levels of phosphate, 10-42% of patients develop some degree of serum hypercalcemia, and 29% are associated with elevated parathyroid hormone (PTH) 9 . The mechanism although uncertain, is probably due to the inactivation of the calcium-sensing receptor and the interference with intracellular second messenger signaling, leading to a primary increased release of PTH, with secondary raise of serum calcium 42 . In a retrospective study, total serum calcium was found to be higher than the reference value in 6% of patients; ionized calcium was higher in 25% and serum PTH in 23% 43 .…”
Section: Thyroid and Parathyroid Disordersmentioning
confidence: 99%
“…In a prospective study, patients who had never previously used lithium had elevated PTH and increased calcium reabsorption along with reduced excretion of calcium, unlike that commonly observed with primary hyperparathyroidism 45 . Multiple case reports associated lithium use and hyperparathyroidism with single or multiple adenomas of the parathyroid glands 42 . A previous study observed that total calcium levels were significantly higher in the lithium-treated group compared to patients who were treated with other psychotropic agents 35 .…”
Section: Thyroid and Parathyroid Disordersmentioning
confidence: 99%